2018
DOI: 10.1002/hep4.1207
|View full text |Cite
|
Sign up to set email alerts
|

L‐Carnitine Suppresses Loss of Skeletal Muscle Mass in Patients With Liver Cirrhosis

Abstract: Liver cirrhosis (LC) is a major cause of secondary sarcopenia. Sarcopenia makes the prognosis worse; thus, novel therapeutic options for sarcopenia in patients with LC are urgently required as they are currently limited. In this retrospective study, 158 patients with LC were screened, and 35 of those patients who were treated with L‐carnitine for more than 6 months and for whom skeletal muscle mass changes could be evaluated by computer tomography were enrolled. Of the 158 patients, 79 patients who did not rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 50 publications
1
86
0
1
Order By: Relevance
“…Carnitine supplementation was recently reported to suppress muscle loss in an initial study of patients with cirrhosis. (46) Key poINtS 1. We believe sarcopenia should not be a sole criterion on which to determine candidacy for LT. 2.…”
Section: A Target Protein Intake Recommendation Proteinmentioning
confidence: 99%
“…Carnitine supplementation was recently reported to suppress muscle loss in an initial study of patients with cirrhosis. (46) Key poINtS 1. We believe sarcopenia should not be a sole criterion on which to determine candidacy for LT. 2.…”
Section: A Target Protein Intake Recommendation Proteinmentioning
confidence: 99%
“…Although controversy remains regarding the accuracy of BIA in patients with ascites, 6,12,13 the psoas muscle mass index (PMI), as assessed using CT, could be an ideal method for patients with chronic liver disease. The PMI is calculated as follows: the sum of the L3 level cross‐sectional area of the right and left psoas muscle mass as identified by manual tracing on CT imaging is divided by the height squared (cm 2 /m 2 ) 14 . With regard to liver disease, various reports have already evaluated skeletal muscle mass using PMI 9,14–18 .…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches, such as branched chain amino acid (BCAA) supplementation, BCAA supplementation and walking exercise, and L‐carnitine treatment, have been reported to prevent the development of skeletal muscle loss in patients with liver cirrhosis. In addition, previous studies have suggested that BCAA supplementation may be useful for maintaining hepatic functional reserve and may help to avoid early discontinuance of sorafenib therapy in patients with HCC receiving sorafenib treatment .…”
Section: Discussionmentioning
confidence: 99%